Zane and the hurricane - Philbrick, W. R. (W. Rodman) (2014)
A twelve-year-old boy and his dog become trapped in New Orleans during the horrors of Hurricane Katrina.
grades 5-7
Keywords: Hurricane Katrina, 2005 -- Juvenile fiction; Hurricane Katrina, 2005 -- Fiction; Survival -- Fiction; Racially mixed people -- Fiction; African Americans -- Fiction; New Orleans (La.) -- Fiction